Evaluation of Prosperity Levels of OECD Countries With Merec-Topsis And Entropy-Topsis Methods (Third Sector Social Economic Review, 2025)
Determining the prosperity levels of countries is an important tool for improving the quality of life of societies and achieving sustainable development goals. Prosperity is shaped not only by economic size but also by social, cultural and environmental factors and is important as a multidimensional concept that determines the general life satisfaction of individuals. In this study, Multi-Criteria Decision Making (MCDM) methods were used to evaluate the prosperity levels of OECD countries. Within the scope of the study, 38 OECD countries were ranked in terms of their prosperity levels and the weights of the criteria were calculated using MEREC (Method based on the Removal Effects of Criteria) and Entropy methods. According to the findings obtained from these two methods, the first three criteria with the highest importance were determined as safety and security, personal freedom and governance, respectively, while the criterion with the lowest importance was health. According to the rankings obtained using MEREC-TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) and Entropy-TOPSIS methods, the three countries with the highest prosperity levels were Denmark, Norway and Sweden, respectively, while the three countries with the lowest prosperity levels were determined as Türkiye, Colombia and Mexico, respectively. As a result of the study, it was determined that the rankings obtained from the analysis were significantly consistent with the ranking obtained from the Legatum Prosperity Index (LPI) Report.
Keywords: Prosperity; Legatum Prosperity Index; TOPSIS Method; MEREC Method; Entropy Method